Taxing Telecommunications in Developing Countries - Matheson, Thornton (IMF Working Papers; Working Paper ;, 2017)
Developing countries apply numerous sector-specific taxes to telecommunications, whose buoyant revenues and formal enterprises provide a convenient 'tax handle'. This paper explores whether there is an economic rationale for sector-specific taxes on telecommunications and, if so, what form they should take to balance the competing goals of promoting connectivity and mobilizing revenues. A survey of the literature finds that limited telecoms competition likely creates rents that could efficiently be taxed. We propose a 'pecking order' of sector-specific taxes that could be levied in addition to standard income and value-added taxes, based on capturing rents and minimizing distortions. Taxes that target possible economic rents or profits are preferable, but their administrative challenges may necessitate reliance on service excises at the cost of higher consumer prices and lower connectivity. Taxes on capital inputs and consumer access, which distort production and restrict network access, should be avoided; so should tax incentives, which are not needed to attract foreign capital to tap a local market.